Effectiveness of treatment with direct-acting antiviral drugs in patients with hepatitis C treated at a referral center in the Pará Sate, Brazil, from 2017 to 2019 - Borges, Francisco das Chagas (2020)
ABSTRACT OBJECTIVE: To evaluate the effectiveness and tolerability of treating hepatitis C with direct-acting antivirals in patients with chronic hepatitis C treated at the Hepatology Outpatient Clinic of Fundação Santa Casa de Misericórdia do Pará, in Belém, Pará State, Brazil. MATERIALS AND METHODS: Cross-sectional study with 305 patients treated with sofosbuvir (SOF), daclatasvir (DCV) or simeprevir (SMV) from May 2017 to March 2019. The medical records of 250 patients who completed treatment during this period were analyzed, of which demographic and clinical data were evaluated. RESULTS: There was a predominance of males (50.40%), mean age of 61.21 years old and from Belém (69.20). Most of them (54.00%) had cirrhosis, and 40.80% reported previous treatment. Genotype 1 was found in 73.60%, and genotype 3 in 23.20% of cases. The standard treatment regimen was SOF, DCV and ribavirin (RBV) for 12 weeks. The rate of sustained virologic response (SVR) was 97.2%. n Four non-responders from genotype 3 and three from genotype 1, using three schemes with SOF+DCV+RBV for 12 weeks; two regimens with SOF+DCV for 12 weeks; a SOF+DCV regimen for 24 weeks; and a regimen with SOF+SMV for 12 weeks. CONCLUSION: The results of this study showed a predominantly urban population, most of them were men and cirrhotic, with a predominance of genotype 1. It is important to notice the good tolerance and high effectiveness of the new direct-acting antivirals with an overall SVR rate of 97.2%.